Investigation into the satisfaction and quality level of online tests from the point of view of Qazvin dental students - Fatemeh Sefidi; Somayeh Rajabizadeh mirak abad; Yosef Anhari; Masumeh Ramezani (مجله ایرانی آموزش در علوم پزشکی, 2022)
Introduction: Access to the Internet and multimedia technologies, has led traditional learning to electronic learning which has made the use of modern evaluation methods in higher education indispensable. Thus, the study was conducted to investigate the quality and satisfaction level of online tests from the point of view of Qazvin dental students (during Corona Epidemic). Methods: This descriptive-analytical study was conducted on 231 students studying at Qazvin Dental School in the academic year 2020 who were selected by enumeration. The instrument was a researcher-made questionnaire in the form of 27 questions in two parts. In the qualitative section, the data were considered based on 5-point Likert scale including ( “very low ”, “low”, “average”, “good” and “great”),and after confirmation of validity and reliability  had been used. Descriptive analysis (Mean, standard deviation and …) and analytical statistics (Spearman correlation coefficent and man Whitney u test) were used to analyze the data. Results: The mean and standard deviation of satisfaction with students' online tests is 3.18±0.52, which is higher than average. Besides, the mean and standard deviation of the quality of online tests from the students' point of view is 3.19 ±0. 51, which is higher than average and indicates students' satisfaction with the quality of this type of evaluation. No significant relationship was found between these components as well as age, gender (P<0.05). Conclusion: The level of satisfaction and quality of online tests from students' point of view is higher than average and indicates students' satisfaction with the quality of this type of evaluation.